HUBUNGAN PENYAKIT PERIODONTAL TERHADAP KELAHIRAN PREMATUR DAN BERAT BADAN LAHIR RENDAH – TINJAUAN PUSTAKA - Erdi Effendi Nasution; Rini Octavia Nasution (Universitas Baiturrahmah, 2022)
Introduction: Periodontal disease can mediate systemic effects through the action of periodontal pathogenic bacteria and lipopolysaccharide will increase prostaglandin and cytokine production which can trigger preterm birth. Pregnant women with periodontitis have a significantly higher risk for preterm birth with low birth weight <37 weeks of gestation and birth weight <2.500 grams. However, periodontal therapy can significantly reduce the rate of premature low birth weight among women with periodontitis. This literature review aims to assess the relationship between maternal periodontal diseases on preterm and low birth weight. Literature Review: Periodontitis can act as a reservoir of microbes and inflammatory mediators that affect preterm birth. Several studies have revealed that mothers with periodontal pathogens will increase levels of IL-1β, IL-6, TNF-α and PGE2 that are produced locally through systemic circulation and induce acute phase response in the liver which is characterized by increased levels of C-reactive protein that can trigger a risk of low birth weight. Periodontitis can be a risk factor for preterm birth due to the presence of proinflammatory bacteria and cytokines in the bloodstream that can invade the membrane and placenta. The effectiveness of periodontal treatment to prevent preterm birth is influenced by the diagnostic severity of periodontitis, microbial community composition, and the period of treatment during pregnancy. Conclusion: Periodontal disease is an independent risk factor for preterm birth. Plaque control procedures during pregnancy can reduce the occurrence of preterm and low birth weight.